International Students Reported for Academic Integrity Violations: Demographics, Retention, and Graduation - Fass-Holmes, Barry (Journal of International Students, 2018)
How many international students are reported for academic integrity violations (AIV), what are their demographics, and how do AIV sanctions affect their retention and/or graduation? Descriptive statistical analyses showed that the number of internationals reported for AIVs at an American West Coast public university increased almost six-fold between academic years 2009–10 and 2013–14. However, that number represented less than 7.5% of these students’ total enrollment. Among reported ones, undergraduates outnumbered graduate students, males outnumbered females, Chinese outnumbered other nationalities, Economics majors outnumbered other majors, and the most common AIV was exam misconduct. More than half who were reported and suspended for AIVs graduated and/or were retained. These findings’ administrative, policy, and theoretical implications are discussed.